RESTORING THE CONCEPT OF AL UMM MADRASATUL ULA WITH CHALET® TOYS - Hartono, Haryani Santo; Pertiwi, Shinta Ayu (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Derived from the famous fragment of Arabic poem, al umm madrasatul ula which means mother as the first school is one of the concepts in home education. A mother, becomes the foundation for the education of children in the family. Because of the generality of a mother at home while the father is working. Following the development of increasingly sophisticated technology today, it is inevitable that its benefits also have disadvantages. Analogically, like a knife which if not used properly, its existence will be destructive. Children's addiction to gadgets is a phenomenon that is now happening a lot of cases. In fact, children only need the full attention of their parents, especially from the mother figure who is more often with them at home. Their greater need for attention from the mother, one of which can be represented by the choice of educational games. One of them is Chalet ® Toys, a home-based Islamic educational game. This study aims to show one way to restore the concept of " al umm madrasatul ula " through the world of children's play, using Islamic edu-games. In this case, using the edu-game Chalet ® Toys as a solution for mothers in carrying out their role as educators at home through home fun religious education.  Chalet ® Toys is not just a game, from it comes a concept that supports the role of mothers to be able to pay more attention to children’s education through fun game media and of course containing religious values.